Taking a closer look at rural education - Marioara Rusu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
In a globalized, knowledge-based economy, education and training is of great importance for increasing economic and social progress: an adequately trained workforce can face competition in terms of productivity, quality and innovation. According to Eurostat, Romania allocates less money to education than most European Union countries. These allocations reflect the low level of attention paid to the education and training system. This paper analyses the situation and trends that have been registered in the Romanian education system in the EU's postaccession period. The set of indicators has been selected to cover both education levels and the types of predominantly rural, intermediate and predominantly urban regions. The following dimensions were considered: participation in education, the human and material resources involved and, where possible, the results.
Keywords: I21; I29; R10; 330; education; rural regions; Romania